Immediate and midterm impact of percutaneous transvenous mitral valve commisurotomy (PTMC) on right ventricular function - Rahman, Mohammad Abdur; Ahsan, Syed Ali; Siddique, Md Abu; Habib, SM Ahsan; Salim, Md Abu; Akhtar, Gulsan; Hossain, Mohammad Mobarack; Khaled, Md Fakhrul Islam; Kabir, Muhammad Faisal Ibn; Moshed, SM Nahid; et al. (University Heart Journal, 2015)
Mitral stenosis (MS) affects right ventricular (RV) function as a result of myocardial and hemodynamic factors. Although the long-term effects of mitral commissurotomy are well known, the aim of this study was to evaluate the immediate and midterm impact of percutaneous mitral commissurotomy (PTMC) on RV function in patients with MS. This is an observational study conducted at University cardiac centre, Bangabandhu Sheikh Mujib Medical University during December 2012 to November 2013 (one year), among 50 patients Patients presenting with mitral stenosis, who fulfill the criteria to PTMC procedure attending Cardiology department of BSMMU during the study period were enrolled in this study whereas, patients with systemic hypertension, diabetes mellitus, more than mild mitral and aortic regurgitation and or aortic stenosis, with history of previous mitral and aortic valve surgery, atrial fibrillation and bundle branch block were excluded from the study. The current study shows female predominance (66%) and majority (68%) of study population were in age group between 36-40 years. 90% of study population presented with fatigue and other symptoms includes shortness of breath (85%), palpitation (65%), chest pain (28%), dizziness (25%), ankle edema (15%) and headache among 10%. Echocardiographic measurement showed, MVA significantly improved immediately and 6 months after PTMC among the study population. Hemodynamic function of the study sample revealed significantly reduction of PASP, PADP and mean PAP immediately and 6 months after PTMC. 2 D echocardiographic parameter of right ventricular systolic function showed RVOTfs%, Tei index significantly improved immediately and 6 months after PTMC.Others parameters of RV systolic function TAPSE, RVFAC and RVEF(2D and 3D) remain stable immediately after but showed significant improvement 6 months after PTMC. There was significant reduction in IVA during the immediate period following PTMC and also after 6 months.. Immediately and 6 months after successful PTMC, significant decrease in RV contractility as assessed by IVA was observed whereas other parameters of infundibular and global RV function as assessed by RVOTfs and Tei index showed significant improvement. TAPSE,RVFAC and RVEF(2D and 3D) remain stable immediately after PTMC but showed significant improvement 6 months after PTMC. Further work using larger numbers of patients is needed to confirm our findings and to assess their utility in patient followup and management. University Heart Journal Vol. 9, No. 2, July 2013; 88-98